Effect of the quinoline-3-carboxamide ABR-215757 during inflammation - Helmersson, Sofia (Lund University Faculty of Medicine Doctoral Dissertation Series, 2013)
ABR-215757 (5757) is a quinoline-3-carboxamide (Q-compound) currently in clinical development for systemic sclerosis. Q-compounds have shown efficacy in several different models of autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE) and collagen induced arthritis. However, the mechanism of action is still poorly understood. In this thesis we have tried to find the mechanism of action of 5757 using different inflammatory models. We studied the effect of 5757 on generation of cells from bone marrow in cultures supplemented with different colony stimulating factors (paper I). CD11c+ cells increased in presence of 5757 while GR1+ cells decreased and also proliferated less in presence of 5757. These results were seen in GM-CSF and M-CSF stimulated cultures but not in cultures stimulated with G-CSF. 5757 did not affect the function of the generated cells. We also studied the effect of 5757 in amelioration of inflammatory disease. We used EAE, the animal model for the human autoimmune disease multiple sclerosis for this purpose (paper II). Treatment of mice with 5757 effectively reduces induction of EAE. This mechanism is an early effect since treatment with 5757 during the first five days after induction also reduced EAE development. Influx of T cells and myeloid cells to CNS was significantly reduced in these mice. EAE is a T cell dependent disease and the activation of antigen-specific disease-causing T cells occurs early in the peripheral lymphoid organs. In vivo proliferation of antigen-specific T cells and production of the effector cytokines IFN-γ and IL-17 were reduced in mice treated with 5757. To study the effect of 5757 on cell migration we used a sterile peritonitis model were necrotic cells or alum were used to induce inflammation (paper III). 5757 reduced migration of inflammatory monocytes and eosinophils to inflamed tissue. We also showed that the effect of 5757 on cell recruitment to inflamed tissue is dependent of Receptor of Advanced Glycation End products (RAGE) and that expression of this receptor by hematopoietic cells is important for the effect of 5757. Taken together this thesis shows that i) 5757 affects generation of immune cells in vitro, ii) 5757 treatment affects T cell activation and thereby reducing EAE and ii) that 5757 reduce migration of inflammatory cells to inflamed tissue in a RAGE-dependent way.